МОДЕЛІ ФОРМ ПРЕДСТАВЛЕННЯ НАВЧАЮЧИХ СУКУПНОСТЕЙ ДЛЯ БАГАТОРІВНЕВИХ СИСТЕМ ДІАГНОСТУВАННЯ ВУЗЛІВ ЕЛЕКТРОТЕХНІЧНОГО ОБЛАДНАННЯ - Мислович, М.В. (Інститут електродинаміки НАН України, Київ, 2021)
The results of consideration of improved mathematical models of vibration diagnostic signals, taking into account both the properties of the diagnostic objects and the modes (speed, electrical temperature, etc.) in which it operates are presented. Models of representation of training sets corresponding to various technical states of units of electrical equipment (EE) for various modes of their operation are considered. A models of representation of training sets in the form of a matrix, the elements of which reflect the ellipses of dispersion of diagnostic attributes of certain types of nodes defects and operating modes of the observed equipment, is proposed. The structure of constructing training sets by flat (2D) and volumetric (3D) matrix, the elements of which contain the sets corresponding to the individual components of EA, and their combination forms a diagnostic description of electrical units, is substantiated. References 18, figures 5.